Tantangan Guru Madrasah Ibtidaiyah Dalam Mengimplementasikan Kurikulum Merdeka: Analisis Kualitatif Berbasis Pendekatan Pedagogis Islami - Siti Uswatun Khasanah (El-Ihsan: Journal of Contemporary Islamic Education, 2025)
This study aims to analyze the challenges faced by Madrasah Ibtidaiyah teachers in implementing the Merdeka Curriculum and to examine the efforts undertaken to address these challenges through an Islamic pedagogical approach. The research employed a descriptive qualitative design, with data collected through interviews, observations, and documentation involving a fourth-grade teacher at MI Aulia Cendekia Pekanbaru. Data analysis was conducted through data reduction, data display, and conclusion drawing.The findings reveal several major challenges encountered by teachers, including difficulties in developing learning documents such as Learning Outcomes, Learning Objectives, Learning Objective Sequences, and teaching modules; limited understanding in selecting appropriate instructional strategies and assessment methods aligned with the characteristics of the Merdeka Curriculum; and a lack of training and technical support from educational institutions. To overcome these challenges, teachers engaged in various efforts, such as participating in Teacher Working Group activities, undertaking independent professional development, and fostering collaboration among teachers. These efforts reflect Islamic pedagogical values, including ikhtiar (earnest effort), amanah (responsibility), and the role of teachers as murabbi in the educational process. This study highlights the importance of strengthening continuous mentoring and professional development for Madrasah Ibtidaiyah teachers to support the implementation of the Merdeka Curriculum in harmony with Islamic educational values.